Structural and Electrical Characterization of the Nickel Silicide Films Formed at 850 °c by Rapid Thermal Annealing of the Ni/Si(1 0 0) Films - Utlu, G.; Tarı, Süleyman; Artunç, N.; Budak, S.; Tarı, Süleyman (Elsevier Ltd., 2010)
Nickel di-silicide formation induced by RTA process at 850 °C for 60 s in the Ni/Si(1 0 0) systems are investigated as a function of the initial Ni film thickness of 7-89 nm using XRD, RBS, SEM, X-SEM and AFM. Based on the XRD and RBS data, in the silicide films of 400-105 nm, NiSi and NiSi2 silicide phases co-exist, indicating that Ni overlayer is completely transformed to NiSi and NiSi2 silicide phases. SEM reveals that these films consist of large grains for co-existence of NiSi2 and NiSi phases, separated from one another by holes, reflecting that NiSi2 grows as islands in NiSi matrix. These films have low sheet resistance, ranging from 1.89 to 5.44 Ω/□ and good thermal stability. For thicknesses ≤ 80 nm RBS yields more Si-rich silicide phases compared to thicker films, whereas SEM reveals that Si-enriched silicide islands with visible holes grow in Si matrix. As the film thickness decreases from 400 to 35 nm, AFM reveals a ridge-like structure showing a general trend of decreasing average diameter and mean roughness values, while sheet resistance measurements exhibit a dramatic increase ranging from 1.89 to 53.73 Ω/□. This dramatic sheet resistance increase is generated by substantial grain boundary grooving, followed by island formation, resulting in a significant phase transformation from NiSi2-rich to Si-rich silicide phases. © 2010 Elsevier B.V. All rights reserved.
Keywords: Silicides; Rapid thermal annealing; Sheet resistance; Thermogravimetric analysis; Thickness-dependent silicide formation